2008
DOI: 10.1098/rspb.2008.0750
|View full text |Cite
|
Sign up to set email alerts
|

A serial founder effect model for human settlement out of Africa

Abstract: The increasing abundance of human genetic data has shown that the geographical patterns of worldwide genetic diversity are best explained by human expansion out of Africa. This expansion is modelled well by prolonged migration from a single origin in Africa with multiple subsequent serial founding events. We discuss a new simulation model for the serial founder effect out of Africa and compare it with results from previous studies. Unlike previous models, we distinguish colonization events from the continued e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
94
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 15 publications
13
94
0
2
Order By: Relevance
“…Like Prugnolle et al [28], we thus made the preliminary assumption that modern humans migrated from this region, which harbours a very high genetic diversity [41 -43], to expand worldwide, as suggested by a number of population genetics studies [38,44 -49], a scenario often referred to as 'Out-of-Africa'. A testable prediction resulting from this model is that modern human populations would have lost genetic diversity through a very large number of small founder effects during their geographical expansion [49], as proposed on the basis of the observation of decreasing diversity from East Africa at neutral autosomal microsatellites [38,46]. This is also what we found in this study, in agreement with Prugnolle et al [28] for the three HLA class I loci HLA-A, -B and -C, and for the first time for the four HLA class II loci HLA-DRB1, -DQA1, -DQB1 and -DPB1.…”
Section: Results (A) Human Leucocyte Antigen Diversity and Geographicmentioning
confidence: 99%
“…Like Prugnolle et al [28], we thus made the preliminary assumption that modern humans migrated from this region, which harbours a very high genetic diversity [41 -43], to expand worldwide, as suggested by a number of population genetics studies [38,44 -49], a scenario often referred to as 'Out-of-Africa'. A testable prediction resulting from this model is that modern human populations would have lost genetic diversity through a very large number of small founder effects during their geographical expansion [49], as proposed on the basis of the observation of decreasing diversity from East Africa at neutral autosomal microsatellites [38,46]. This is also what we found in this study, in agreement with Prugnolle et al [28] for the three HLA class I loci HLA-A, -B and -C, and for the first time for the four HLA class II loci HLA-DRB1, -DQA1, -DQB1 and -DPB1.…”
Section: Results (A) Human Leucocyte Antigen Diversity and Geographicmentioning
confidence: 99%
“…However, to interpret genetic clines is delicate as such clines may be explained by very different mechanisms (Fig. 4): demic diffusion with admixture between genetically distinct populations (Ammerman and Cavalli-Sforza 1984), serial founder effects (Deshpande et al 2009), isolation-bydistance where gene flow happens between neighboring populations (Novembre and Stephens 2008;Reich et al 2008), or even differential adaptation to distinct environments, including varying prevalence of infectious diseases (Suo et al 2011). In the current state of research, no definitive conclusion on the genetic clines observed in East Asia has been reached.…”
Section: Interpretation Of Genetic Results and Methodsological Issuesmentioning
confidence: 99%
“…Intuitively, when a new colony is founded, it carries only a subset of the diversity from the previous colony, and therefore, a heterozygosity decrease occurs. Thus, it has been shown that, if the source is placed in Africa, then the prediction of serial founder models matches the observed pattern of heterozygosity (14,22,23). It has also been suggested that the serial founder model can explain worldwide patterns in LD and the ancestral allele frequency spectrum (15, 16), although these claims have not yet been verified in simulations of the model.…”
mentioning
confidence: 96%
“…This collection of models includes coalescent-based migration models that proceed retrospectively in time and that are easily simulated, but that involve relatively few populations, each of which typically represents a large geographic region (11,(17)(18)(19). It also includes models that permit complex phenomena and multiple populations per continent through a prospective approach, but that are often limited in terms of computation time and applicability to statistical inference (14,(20)(21)(22).One model that has performed well in explaining the decline of heterozygosity with increasing distance from Africa is a model of serial founder events beginning from an African origin (14,22,23). In this model, starting with a single source population, a new population is formed from a subset of the individuals in the founding population.…”
mentioning
confidence: 99%